Sequence, structure and evolution of the ecdysone-inducible Lsp-2 gene of Drosophila melanogaster. - Mousseron-Grall, S.; Kejzlarova-Lepesant, J.; Burmester, T.; Chihara, C.; Barray, M.; Delain, E.; Pictet, R.; Lepesant, J.A. (European Journal of Biochemistry, 1997)
The Lsp-2 gene encodes a major larval serum protein (hexamerin) of Drosophila melanogaster. Transcription of Lsp-2 is controlled by 20-hydroxyecdysone. Here we report the analysis of the structure of the Lsp-2 gene including the adjacent 5' and 3' sequences. In contrast to all other known hexamerin genes, Lsp-2 does not contain an intron. The Lsp-2 mRNA measures 2312 bases, as deduced from experimental determination of the transcription-start and stop sites and conceptual translation results in a 718 amino acid hexamerin subunit, including a 21-amino-acid signal peptide. While the calculated molecular mass of the native 697-amino-acid subunit is 83.5 kDa, mass spectrometry gave a value of 74.5 kDa. We detected in the Lsp-2 gene a 2052-bp antisense ORF that probably does not code for any protein. An unusual accumulation of rarely used codon triplets was found at the 5' and 3' ends of the Lsp-2 ORF. The calculated secondary structure matches well with that of arthropod hemocyanins. Electron micrographs show for LSP-2 hexamers a cubic shape, which can not be easily reconciled with its hexameric structure. Phylogenetic analysis revealed that LSP-2 diverged from the LSP-1 like hexamerins after separation of the Diptera from other insect orders.